Virtual reality as a way to good business - Mošorinski Predrag (Trendovi u Poslovanju)
A virtual economy is the emergent property of the interaction between participants in a virtual world. As businesses compete in the real world, they also compete in virtual worlds. Many companies now incorporate virtual world as a new form of advertising. There are many advantages to using these methods of commercialization. The use of advertising within virtual world is a relatively new idea, due to Virtual World as a relatively new technology. According to trade media company Virtual Worlds Management, commercial investments in the virtual sector were in excess of USD 425 million in 2007, and USD 594 million in 2008. During the last year, investments made were approximately 1 billion US $. Investment in marketing and virtual commercials, in Republic of Serbia was about 840 million euros during the last few years.